2010
DOI: 10.4007/annals.2010.172.2135
|View full text |Cite
|
Sign up to set email alerts
|

Heegner divisors,L-functions and harmonic weak Maass forms

Abstract: Recent works, mostly related to Ramanujan's mock theta functions, make use of the fact that harmonic weak Maass forms can be combinatorial generating functions. Generalizing works of Waldspurger, Kohnen and Zagier, we prove that such forms also serve as "generating functions" for central values and derivatives of quadratic twists of weight 2 modular L-functions. To obtain these results, we construct differentials of the third kind with twisted Heegner divisor by suitably generalizing the Borcherds lift to harm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
248
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 155 publications
(250 citation statements)
references
References 40 publications
1
248
0
1
Order By: Relevance
“…Zwegers's thesis has sparked a flurry of recent activity involving such Maass forms. Indeed, harmonic Maass forms are now known to play a central role in the study of Ramanujan's mock theta functions, as well as other important mathematical topics: Borcherds products, derivatives of modular L-functions, GrossZagier formulas and Faltings heights of CM cycles, partitions,and traces of singular moduli (see Bringmann and Ono [5;6], Bringmann, Ono and Rhoades [7], Bruinier [8], Bruinier and Funke [9], Bruinier and Ono [10], Bruinier and Yang [12], Ono [40], Zagier [55] and Zwegers [56]). …”
Section: Introduction and Statement Of Resultsmentioning
confidence: 99%
“…Zwegers's thesis has sparked a flurry of recent activity involving such Maass forms. Indeed, harmonic Maass forms are now known to play a central role in the study of Ramanujan's mock theta functions, as well as other important mathematical topics: Borcherds products, derivatives of modular L-functions, GrossZagier formulas and Faltings heights of CM cycles, partitions,and traces of singular moduli (see Bringmann and Ono [5;6], Bringmann, Ono and Rhoades [7], Bruinier [8], Bruinier and Funke [9], Bruinier and Ono [10], Bruinier and Yang [12], Ono [40], Zagier [55] and Zwegers [56]). …”
Section: Introduction and Statement Of Resultsmentioning
confidence: 99%
“…We will also find that the function M f k (z), the holomorphic projection of R f k (z), has coefficients c + f k (n), and is given by The theory of harmonic weak Maass forms and mock theta functions is of great current interest. See, for example, the works [3], [4], [5], [6], [7], [8], [9], [13]. Let λ ∈ {1/2, 3/2}.…”
Section: Introduction and Statement Of Resultsmentioning
confidence: 99%
“…Recent interest in harmonic weak Maass forms began with their systematic treatment by Bruinier and Funke [13]. Following their appearance in the theory of mock theta functions due to Zwegers [40], it has been shown that harmonic weak Maass forms have applications ranging from partition theory (for example [2,4,6,9,11]) and Zagier's duality [39] relating "modular objects" of different weights (for example [10]) to derivatives of L-functions (for example [14,15]). They also arise in mathematical physics, as recently evidenced in Eguchi et al [16] investigation of moonshine for the largest Mathieu group M 24 .…”
Section: Introduction and Statement Of Resultsmentioning
confidence: 99%